2006
DOI: 10.1111/j.1365-3091.2006.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of Jurassic accretionary complex: Mino terrane, inner zone of south‐west Japan – implications for palaeogeography of eastern Asia

Abstract: Provenance and tectonic history of the Jurassic accretionary complex, Mino terrane, located in the Inner Zone of south-west Japan, were studied using sandstone framework composition and mudrock geochemistry. Modal analysis of sandstones shows that the tectonic setting of the source area for the studied Mino terrane clastic rocks was uplifted basement, largely dominated by highgrade metamorphic terrain composed of quartz and feldspar, especially plagioclase. The textural and mineralogical immaturity, extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 73 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…= 69) shales may reflect recycling, considering that much of these sediments were derived from the Jurassic Mino accretionary complex (terrane) in SW Japan (Chang et al, 1990;Kamata et al, 2000;Mitsugi et al, 2001;Lee and Kim, 2005). Joo et al (2007) described the geochemistry of the Jurassic Mino terrane sediments, and showed that Mino terrane sands and muds exhibit a dispersed trend in A-CN-K space, from granodiorite source towards illite (CIA: 44-78) indicative of non-steady state weathering conditions in the source area. This interpretation suggests that recycling was a significant process during deposition of the Donghwachi and Gisadong shales, and that recycling of fine-grained rocks may mask the weathering history of the source terrain.…”
Section: Figmentioning
confidence: 97%
See 3 more Smart Citations
“…= 69) shales may reflect recycling, considering that much of these sediments were derived from the Jurassic Mino accretionary complex (terrane) in SW Japan (Chang et al, 1990;Kamata et al, 2000;Mitsugi et al, 2001;Lee and Kim, 2005). Joo et al (2007) described the geochemistry of the Jurassic Mino terrane sediments, and showed that Mino terrane sands and muds exhibit a dispersed trend in A-CN-K space, from granodiorite source towards illite (CIA: 44-78) indicative of non-steady state weathering conditions in the source area. This interpretation suggests that recycling was a significant process during deposition of the Donghwachi and Gisadong shales, and that recycling of fine-grained rocks may mask the weathering history of the source terrain.…”
Section: Figmentioning
confidence: 97%
“…EM 1: Precambrian gneissic-granitic rock (Hong, 1992); EM 2: Triassic Yeongdeok Granite (Kim, 2002); EM 3: average clastic rocks of the Mino accretionary complex, SW Japan (Joo et al, 2007); EM 4: Triassic chert of the Mino accretionary complex, SW Japan (Shimizu et al, 2001); EM 5: Chaeyaksan basaltic rock (Kim et al, 1999).…”
Section: Figmentioning
confidence: 98%
See 2 more Smart Citations
“…1980; Kimura & Hori 1993) and is composed of turbidite sandstone–shale successions. Joo et al. (2007) studied turbidite sandstones and revealed that more than 55% of the framework grains in the sandstones are feldspar, followed by about 30% quartz.…”
Section: Middle Jurassicmentioning
confidence: 99%